IMPROVING QUALITY OF LIFE AT EDERLY PEOPLE, THROUGH GIMN ACTIVITIES - Ganciu Mihaela; Ganciu Oana Maria (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
In light of permanent education, physical education and sports activities should be integrated throughout life. The objective of the research is to improve the quality of life of older people to the initiation of maintenance programs by simple methods, reliable and inexpensive. Therapeutic strategies will be adapted practitioners age, associated diseases, profession. The sample under investigation comprised 30 elderly people who participated in two gymnastics lessons a week and a society dance lesson. Inspection methods that I used: bibliographic study, experimental method, survey method and statistical method - mathematical and graphical representation. Quality of life assessment was done by assessing exercise capacity, the survey method and the call routed. Through a sustained program and rhythmic exercise improves cardiovascular activity, as evidenced by increased exercise capacity by lowering resting heart rate, a major component of cardiovascular disease prevention. Decrease abdominal fat and increased muscle tone abdominal favorable effects on biomechanics of the lumbar spine dynamics can thus be considered to be the prevention of back pain. In summary the study conducted, in order to highlight the benefits of the sport for optimal physical condition and fight aging, it can be concluded that physical activity has a beneficial role for the body, both physically and mentally. Survey conducted among people aged III revealed the following: Practicing the sport of gymnastics in a systematic, consistent results in improving health and fitness as well as comfort, good mood, optimism, improving intellectual activity. In short, we can say that these people the sport of gymnastics has improved quality of life.